Political rents in the European Union's agriculture = Wspólna Polityka Rolna a renty polityczne - analiza komparatywna na podstawie wybranych krajów Unii Europejskiej - Czyżewski, Bazyli; Brelik, Agnieszka (Zielona Góra: Faculty of Economics and Management Press)
Occurrence of land rents in modern agriculture of the EU is confirmed by the long-lasting upward trend in agricultural land prices. However, a question arises whether these rents are differential ones, linked with a different productivity of agricultural land, absolute ones in the classical sense, or political rents in the meaning of the public choice theory? The objectives of the article are mainly theoretical.
Keywords: renta gruntowa; renta polityczna; rolnictwo; Wspólna Polityka Rolna UE; ground; political rent; agriculture; CAP of the UE; sustainable development